A150 IS FOCAL ACTIVE COLITIS OF GREATER SIGNIFICANCE IN PEDIATRIC PATIENTS? A RETROSPECTIVE REVIEW OF 68 CASES WITH CLINICAL CORRELATION. (1st March 2018) - Ashok, D; Osmond, A; Francouer, C; Miller, M; Walsh, J
Abstract: Background: Focal active colitis (FAC) is a histopathologic finding of uncertain clinical significance in individual patients. In adult cases, infection accounts for approx. 50%, Crohn's disease (CD) for 0–13%, and 20–30% are idiopathic (likely related to bowel preparation). One previous study of 29 cases of pediatric FAC showed a 28% rate of CD. Histologic features to distinguish between idiopathic FAC and inflammatory bowel disease (IBD) related FAC have not been determined. Aims: Our study aimed to review a large cohort of pediatric patients with FAC to determine what proportion of them had IBD, and whether there was an amount or pattern of inflammation that predicted IBD. Methods: Sixty eight biopsy sets from 68 patients aged ≤18 years with FAC were identified and reviewed retrospectively. Patients with a prior diagnosis of IBD or chronic colitis in the index biopsies were excluded. Original slides were assessed for a number of inflammatory criteria. Clinical data including presenting symptoms, medication history and final diagnoses were recorded. Data were analysed using Pearson correlations and Fisher's exact chi-square analyses. Results: Sixteen patients (24%) had a final diagnosis of IBD. When cases with terminal ileal inflammation and / or granulomas were excluded 6 of 54 remaining patients had a final diagnosis of IBD (11%). A final diagnosis of IBD was significantly associated with the presence of crypt abscesses in patients with and without terminal ileal inflammation (Fisher's exact=5.67, p=0.027 and Fisher's exact=7.99, p=0.025) and the presence of one or more elevated serum inflammatory markers (Fisher's exact=11.44, p=0.001 and Fisher's exact=15.02, p=0.001). IBD was significantly associated with TI inflammation (Fisher's exact=20.27, p<0.001). An amount or pattern of inflammation that could be used to predict IBD was not determined. Conclusions: In keeping with the previous pediatric study, this study demonstrated a 24% rate of IBD in pediatric patients with FAC; however, when patients with associated terminal ileal inflammation and / or granulomas were excluded, the rate was 11%, similar to the reported rates in adults. When TI inflammation is present in association with FAC there is a high probability of IBD (10/14 cases, 71%). In all patients, the presence of crypt abscesses or increased serum inflammatory markers is associated with a higher likelihood of IBD. In pediatric patients whose biopsies show FAC without terminal ileal inflammation, the clinical implications appear to be the same as those in the adult population and do not warrant more aggressive follow up. Funding Agencies: None